Indonesia’s Response to Sovereignty Threats in the Natuna Sea under UNCLOS 1982 - Zakiah Reski Maharani Zuhdy (Indonesian Maritime Researchers and Lecturers, 2025)
This region faces significant legal and geopolitical challenges due to the maritime conflict in the South China Sea, particularly China's unilateral claims over vast areas based on the Nine-Dash Line. This essay evaluates the direct impact of China's claims on Indonesia's sovereign rights, particularly in the North Natuna Sea, while critically examining the legitimacy of those claims in the context of the United Nations Convention on the Law of the Sea (UNCLOS) 1982. It is clear from legal precedents such as the 2016 ruling of the Permanent Court of Arbitration (PCA) that the Nine-Dash Line is baseless under UNCLOS, which rejects historical claims as a legitimate basis for maritime rights. China's claimed maritime borders have included portions of Indonesia's Exclusive Economic Zone (EEZ), which has resulted in frequent incursions by Chinese coast guard and fishing vessels. This has put Indonesia's maritime sovereignty, national security, and marine-based economy at risk. Indonesia has responded with a multi-pronged approach that includes deploying maritime forces to exert sovereignty over the disputed waters, strengthening domestic law in accordance with UNCLOS, and submitting diplomatic protests to the UN. Additionally, Indonesia is still pushing through ASEAN procedures for a regional code of conduct that is legally obligatory. The results highlight the international legal foundation of Indonesia's legal and policy responses and uphold UNCLOS's dominance as the main legal framework for maritime governance and dispute settlement in the Indo-Pacific area.